Protein kinase C and protein kinase A are involved in the protection of recombinant human glucagon‐like peptide‐1 on glomeruli and tubules in diabetic rats - Yin, Weiqin (J Diabetes Investig, 2018)
AIMS/INTRODUCTION: Blockade or reversal the progression of diabetic nephropathy is a clinical challenge. The aim of the present study was to examine whether recombinant human glucagon‐like peptide‐1 (rhGLP‐1) has an effect on alleviating urinary protein and urinary albumin levels in diabetic rats. MATERIALS AND METHODS: Streptozotocin‐induced diabetes rats were treated with rhGLP‐1 insulin and saline. Using immunostaining, hematoxylin–eosin, electron microscopy and periodic acid–Schiff staining to study the pathology of diabetic nephropathy, and we carried out quantitative reverse transcription polymerase chain reaction, western blot and immunohistochemistry to identify the differentially expressed proteins. The mechanism was studied through advanced glycation end‐products‐induced tubular epithelial cells. RESULTS: rhGLP‐1 inhibits protein kinase C (PKC)‐β, but increases protein kinase A (PKA), which reduces oxidative stress in glomeruli and in cultured glomerular microvascular endothelial cells. In tubules, rhGLP‐1 increased the expression of two key proteins related to re‐absorption – megalin and cubilin – which was accompanied by downregulation of PKC‐β and upregulation of PKA. On human proximal tubular epithelial cells, rhGLP‐1 enhanced the absorption of albumin, and this was blocked by a PKC activator or PKA inhibitor. CONCLUSIONS: These findings suggest that rhGLP‐1 can reverse diabetic nephropathy by protecting both glomeruli and tubules by inhibiting PKC and activating PKA.